Ampicillin in the treatment of brucellosis: A controlled therapeutic trial - McDevitt, D. G. (1970)
McDevitt, D. G. (1970).Brit. J. industr. Med.,27, 67-71. Ampicillin in the treatment of brucellosis: A controlled therapeutic trial. A controlled therapeutic trial has been carried out with ampicillian in the treatment of brucellosis. Sixty-eight people, veterinary surgeons or their unqualified assistants, with serological evidence of brucella antibodies measured by the anti-human globulin (Coombs) test and the complement-fixation test, some of whom had symptoms consistent with a diagnosis of brucellosis, were treated in two random groups. One group was given ampicillin, 1 g. four times a day for 28 days; the other took a placebo in identical capsules for the same period. The response to treatment was gauged by subjective improvement in symptoms four weeks after its completion and by serological improvement after four months. Fifty-four people completed the trial. There was no evidence that ampicillin was any more effective than the placebo in treatment, either symptomatically or serologically, but 25% of the people in both treatment groups reported subjective symptomatic improvement. It is suggested, therefore, that subjective improvement alone is an inadequate criterion for assessing response to treatment in culturally unproven brucellosis, and that, because of this, current conventional therapies may require critical revaluation. Similarly, a subjective therapeutic response cannot be relied upon for diagnostic confirmation in a patient in whom the diagnosis is uncertain.